노화와 억제 능력의 관계: 웹기반 숫자 스트룹 과제로부터의 증거 - 태진이; 이윤형; 최원일; Jini Tae; Yoonhyoung Lee; Wonil Choi (인지과학, 2025)
The aim of this study is to examine age-related differences in inhibitory control using a Number Stroop task. Participants, ranging from 20 to 69 years old, were presented with number strings composed of digits from 1 to 4, displayed in quantities ranging from one to four (e.g., "33" or "333"). The stimuli were categorized into congruent (e.g., "333") and incongruent conditions (e.g., "33"). In the congruent condition, the number of digits and the digit itself matched, leading to minimize interference, whereas in the incongruent condition, the number of digits and the digit itself differed, requiring conscious suppression of distractor interference. When a number string was presented, participants were asked to report the number of digits, while ignoring their numerical meaning. The results showed that response times increased with age, and responses were slower in incongruent trials compared to congruent trials. A significant interaction between age and the Stroop effect was observed, particularly between individuals in their forties and fifties. Specifically, while there was no significant difference in response times between these age groups in the incongruent conditions, participants in their fifties exhibited slower response times than those in their forties in the congruent conditions. This suggests that as cognitive abilities decline with aging, individuals in their fifties adopt a more cautious approach even in the easier, congruent trials. Furthermore, analyses using the diffusion model for conflict tasks (DMC) revealed that older participants tended to employ more cautious strategies during task performance. This study demonstrates that declines in inhibitory control become more pronounced starting in the fifties, leading to a shift toward more cautious task execution strategies, which is particularly evident in easier task conditions. Additionally, by utilizing experimental data from various age groups, the modeling analysis provided insights into how task performance strategies change across different age groups, allowing for a more comprehensive understanding of age-related changes in inhibitory task performance. 본 연구의 목적은 방해 자극에 대한 억제 능력을 측정하는 숫자 스트룹(Number Stroop) 과제를 사용하여 연령에 따른 억제 능력의 차이를 알아보는 것이다. 참가자들은 20세부터 69세까지의 성인들로, 이 과제의 자극으로는 1에서 4까지의 숫자들이 1개에서 4개 사이로 구성된 숫자열이 제시되었다. 제시되는 숫자열은 일치 조건과 불일치 조건으로 구분되는데, 일치 조건(예: 333)은 숫자열을 구성하고 있는 숫자와 자극의 개수가 같은 자극으로 두 개의 정보가 같으므로 간섭이 최소화된다. 이에 반해 자극의 숫자와 개수가 다른 불일치 조건(예: 33)은 의식적으로 방해 자극의 영향을 억제하면서 목표 정보에 주의를 두어야 하므로 일치 조건에 비해 의식적인 억제 정보처리가 요구된다. 이 실험에서 참가자들은 제시되는 숫자열(예: 33)을 보고 자극의 속성(예: 3)이 아니라 자극의 개수(예: 두 개)를 최대한 빠르고 정확하게 보고하는 과제를 수행했다. 연구 결과, 연령이 증가할수록 과제 수행 시간은 늘어났고, 일치 조건에 비해 불일치 조건의 수행 시간이 느려졌다. 참가자의 나이와 스트룹 효과의 크기 간의 상호작용 효과는 40대와 50대 사이에서만 유의미했다. 보다 구체적으로 불일치 조건에서는 두 연령 집단의 반응시간 차이가 없었던데 반해, 일치 조건에서는 50대가 40대에 비해 느리게 반응하는 특성이 관찰되었다. 이는 50대 성인들이 노화로 인해 인지 능력이 저하됨에 따라 상대적으로 쉬운 일치 조건에서도 더 신중하게 판단하고 있음을 시사한다. 또한 갈등 과제를 위한 확산 모형(DMC)을 이용한 분석결과에서도 나이가 들수록 과제 수행 상황에서 더욱 신중한 전략을 취하는 경향이 나타났다. 본 연구는 노화에 따른 억제 능력의 감소가 50대부터 두드러지며, 이러한 인지 변화가 과제 수행 시 신중한 전략을 사용하도록 하는데, 이는 일치 조건과 같이 더 쉬운 과제 상황에서 뚜렷이 나타날 수 있음을 보여주었다. 나아가, 다양한 연령대의 참가자가 참여한 실험 데이터를 바탕으로 한 모델링 분석을 통해 연령 집단별 과제 수행 전략의 변화를 확인함으로써, 노화에 따른 억제 과제 수행 방식의 변화를 종합적으로 이해할 수 있었다.